Le role du droit romain dans l`education juridique de la Republicque de Macedoine - Mirjana Polenak-Akimovska; Vlado Buckovski; Goce Naumovski; Esin Kranli (IUS ROMANUM, 2016)
Roman law has a clear place in the legal system of countries in Europe. The legal system of the Republic of Macedonia belongs to the Romano-German group. The study of Roman law in law faculties is based on a number of reasons - scientific, educational, didactic and cultural. It has been taught at the Faculty of Law in Skopje since its establishment as a historical-legal discipline. The article discusses the prospects for development of the roman law in contemporary legal education.
Keywords: Roman law, teaching, Republic of Macedonia